AN ECONOMIC ANALYSIS OF KENYA'S HORTICULTURE EXPORT PERFORMANCE 2010 - 2021 - Nzomoi, Joseph; Mutua, Japheth; Kiprop, Hosea; Kathambi, Albina (International Journal of Economics, 2022)
Purpose: The horticulture sector in Kenya has consistently dominated agricultural sector's contribution to the economy's GDP growth over the last two decades. This paper assesses the export performance of horticulture sector's three main components of cut flowers, fruits and fresh vegetables for the period 2010 - 2021. The paper also sought to identify the challenges that affect the horticulture sector and propose ways of addressing the challenges. Methodology: The study utilized secondary annual time series data collected from the Kenya National Bureau of Statistics, the Central Bank of Kenya and the Food and Agriculture Organization of the United Nations. Descriptive statistics were used to analyze the data and draw inferences and conclusions. Findings: The study shows that the value of export revenues from cut flowers have been consistently higher than the earnings from fruits and fresh vegetables for the twelve year period from 2010 to 2021 with the highest earnings being recorded in 2018 when the subsector earned Ksh 113 Billion. Fresh vegetables recorded higher earnings than fruits over the same period, except for the year 2021 when fruit earnings were higher (at Ksh 27 Billion) than earnings from fresh vegetables (at Ksh 18 Billion). This is despite the fact that fruit volumes were lower than the vegetable volumes, implying that the export prices for the fruits were much better than the vegetable prices. Results also show that when real GDP dipped to negative 0.3 per cent in 2020 mainly due to the effects of COVID 19, horticulture export earnings stood at Ksh 151 Billion, perhaps a display of sectoral resilience to the adverse economic effects associated with COVID 19. There does not seem to be a clear relationship between real GDP growth and export earnings from horticulture products during the ten-year period of analysis. This tends to invalidate the export-led growth hypothesis. Key challenges facing the sector include overreliance on the EU market, pest infestation, low production and productivity and high cost of airfreight. Unique Contribution to Theory, Practice and Policy: Based on these findings, the paper concludes that Kenya's export performance is way below its potential and recommends increased production to meet global demand and diversification of markets and product range.